Pertanggungjawaban Pelaksana Operasional Badan Usaha Milik Nagari (BUMnag) Gadut Sejahtera Nagari Gadut Kecamatan Tilatang Kamang - Hamidi, Syahrul; Azheri, Busyra; Fauzi, Wetria (Universitas Ekasakti, 2023)
The operational implementation of BUMNag Gastra experienced various problems which made it difficult to develop properly. These problems include, among others, the Human Resources Manager is still low, resulting in one of the accountability BUMNag not being carried out properly. Therefore the author examines the following problem formulation: 1) How is the Operational Implementation of BUMNag Gastra Nagari Gadut 2) What is the accountability of the Operational Executive of BUMNag Gastra Nagari Gadut. The research method that the author uses is Juridical Empirical, namely research that focuses on how the implementation of BUMNag Gastra Nagari Gadut operations in the field. The results of the research are presented in the form of descriptive analysis relying on primary data in the form of field data (interviews) supplemented by secondary data. As for the results of the author's research, it can be concluded, firstly, the operational implementation of BUMNag Gastra Nagari Gadut is still simple and not fully in accordance with management functions. The two accountability reports have not been properly presented, so they are not in accordance with legal objectives, namely certainty and justice. In the future, efforts are expected to promote BUMNag, namely 1) increasing human resources 2) increasing capital 3) instilling a sense of ownership of BUMNag which is still low. 4) improvement of facilities and infrastructure